2007
DOI: 10.1021/ic700360a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Cationic Bidentate Lewis Acid

Abstract: As part of our efforts to increase the fluoride affinity of bidentate Lewis acids, we have set out to determine if the F(-) anion chelation occurring in such systems can be complemented by favorable Coulombic attractions. To explore this idea, the neutral B/Hg bidentate Lewis acid 1-{Mes(2)B}-8-{(2,6-Me(2)-4-Me(2)NC(6)H(2))Hg}C(10)H(6) (3) and its cationic analogue [1-{Mes(2)B}-8-{(2,6-Me2-4-Me(3)NC(6)H(2))Hg}C(10)H(6)]+ ([4]+) have been synthesized and studied. Compound 3 as well as the triflate salt of [4]+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 26 publications
1
47
0
Order By: Relevance
“…49,51,52 These heteronuclear bifunctional boranes have been characterized by conventional means including 199 Hg NMR spectroscopy. In the case of 11, the 199 Hg NMR signal, which appears at 741.9 ppm, is split into a triplet of triplets as a result of coupling with fluorine nuclei of the pentafluorophenyl group ( 3 J Hg-F ) 499 Hz and 4 J Hg-F ) 165 Hz).…”
Section: B/hg Heteronuclear Multidentate Lewis Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,51,52 These heteronuclear bifunctional boranes have been characterized by conventional means including 199 Hg NMR spectroscopy. In the case of 11, the 199 Hg NMR signal, which appears at 741.9 ppm, is split into a triplet of triplets as a result of coupling with fluorine nuclei of the pentafluorophenyl group ( 3 J Hg-F ) 499 Hz and 4 J Hg-F ) 165 Hz).…”
Section: B/hg Heteronuclear Multidentate Lewis Acidsmentioning
confidence: 99%
“…In water, the emission band is centered at 458 nm for [p-16] + and 433 nm for [o-16] +(Figure 10) giving rise to a distinct blue color, which can be detected with the naked eye at micromolar concentrations. In the case of [p-16] + , the blue emission is readily quenched upon addition of 1 equiv of cyanide, which binds to the boron center thereby disrupting the frontier orbitals (Figure 11).To verify whether the Coulombic effects could be used to increase the anion affinity of chelating bifunctional boranes, the heteronuclear B/Hg compound 12 was converted into the corresponding ammonium triflate salt[17]OTf by reaction with MeOTf (Scheme 10) 52. As shown by DFT calculations, conversion of the amino group into an ammonium group on going from 12 to [17] + results in a lowering of the mercury vacant orbitals, allowing them to mix more efficiently with the boron orbital.…”
mentioning
confidence: 99%
“…Studies of several groups have demonstrated that boron based receptors that are bidentate and cationic capitalize on both Coulombic and cooperative effects leading to a further enhancement of their F  affinity. Consequently, F  detection in aqueous media could be realized [37][38][39][40]. In order to recognize F  in water solution, Gabbaï et al [37][38][39][40] developed a number of cationic boranes (40-44 in Figure 12).…”
Section: Fluoride Detection In Aqueous Mediamentioning
confidence: 99%
“…Consequently, F  detection in aqueous media could be realized [37][38][39][40]. In order to recognize F  in water solution, Gabbaï et al [37][38][39][40] developed a number of cationic boranes (40-44 in Figure 12). These compounds were able to bind with F  in organic solvent/ water mixed solution with high sensitivity and selectivity.…”
Section: Fluoride Detection In Aqueous Mediamentioning
confidence: 99%
“…However, we would like to acknowledge and cite some leading references on topics that have been put aside deliberately. These include principally, but not exclusively, the work on:·ferrocenylboranes (and other related compounds) and the study of the M-B interaction in these complexes; [12] group IV metallocenylboranes and the study of zwitterionic complexes in ZieglerNatta polymerization; [13] the hydroboration of olefin-containing metallocenes; [14] the electrophilic attack of dienes and alkyl groups by Lewis acids; [15] boryls, borylenes and other metal-bonded boron species; [16] some bidentate Lewis acids; [17] multimetallic species containing bridging boronates. [18] Coordination of Base-Free Amphoteric Ligands…”
Section: Introductionmentioning
confidence: 99%